The challenges of non-resident students in UiTM Kota Kinabalu/ Nixon Henry, Joenyez Noel Placidus and Haijon Gunggut - Henry, Nixon; Placidus, Joenyez Noel; Gunggut, Haijon (Universiti Teknologi MARA, Sabah, 2024)
This article focuses on the challenges encountered by nonresident students in Universiti Teknologi MARA Sabah Branch in Kota Kinabalu, particularly students renting houses. The objectives involve identifying challenges faced by non-resident students. Employing a quantitative method, questionnaires were given to all non-resident students in the Non-Resident Students Telegram group (375 students). However, only 130 non-resident students filled out the questionnaire. The results show that the top challenges were finding a suitable house to stay in, difficulty in finding accommodation that is both cheap and near the campus, experiencing financial burden because of staying off-campus, and challenges in managing expenses and transportation reliability. The results also suggest that feeling lonely is the least likely challenge for non-resident students. The results offer valuable insights to the non-resident students in UiTM Sabah Branch, Kota Kinabalu, so that the support systems tailored to the specific needs of non-resident students can be enhanced. Overall, the challenges faced by non-resident student respondents in UiTM Sabah Branch, Kota Kinabalu, may not be too serious.